Propagation of Random Errors Along an Analogic Aerial Triangulation Strip - Franco, A. Dos Santos (The International Hydrographic Review, 2015)
From the reports on the International Congress of Photogrammetry held in Lisbon in September 1964 one can see that discussions on the merits of analytical versus analogic aerial triangulation are far from being exhausted. Thus I believe further study of error propagation along a strip of analogic aerial triangulation is still useful. The majority of the explanations on this subject that I know of are usually difficult to follow because the excessive amount of algebra hides the main physical aspect of the problem. Hence I propose in this article to derive the formulae expressing the propagation of accidental errors directly from the double accumulation of these errors.